The Effect of Product Quality and Price on Purchase Decisions Through Influencer Marketing - G, Fikram; Khaddapi, Muammar; Qamaruddin, Muh. Yusuf (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of product quality and price on purchasing decisions mediated by influencer marketing at the R2 Sport store in Palopo City. The phenomenon shows an increase in promotional activities through social media by involving local influencers, along with the increasing competition in the sports equipment business in the area. However, not all of the increased promotions have been able to increase consumer purchasing decisions directly. This study uses a quantitative approach with a survey method of 100 respondents who are active customers. Data were analyzed using path analysis techniques to test direct and indirect relationships between variables. The study results show that (1) Product quality positively and significantly affects influencer marketing. (2) Price has a positive and significant effect on influencer marketing. (3) Product quality positively and significantly affects Purchasing decisions. (4) Price has a positive and significant effect on purchasing decisions. (5) Influencer marketing positively and significantly affects Purchasing decisions. (6) By using influencer marketing as an intervening variable at the R2 Sport Palopo Store, product quality and price positively and significantly affect Purchasing decisions.